A study of the implementation of procurement management system to a project success in mega project construction in Malaysia : a case study of Kuala Lumpur International Airport 2 (KLIA2) - Noor Hanira, Mahidin (2014)
Procurement management system is very important in any industries area especially in construction area. Procurement is a highly skilled profession. It is focuses on people the knowledge, skills and capabilities either both of the public and private sector. It is because to implement procurement to innovation and ensure that these are required level of achievement. By managing a success project, it can help to minimize the risk of a project. The purpose of this study is to the implementation of procurement management system to a project success in mega project construction in Malaysia. Procurement management systems were examined to see the related between Project Management Body of Knowledge (PMBOK) and procurement management system in KLIA2. This study also identified the failure factors in procurement management in KLIA2. In conducting the research, questionnaires were collected in interview with forth respondents in Malaysian Airport Holdings Berhad (MAHB), UEM Construction Berhad and LKHDM Sdn. Bhd. The data already recorded, then analyzed through breaking down the point. The data also collected from secondary data which adhered from website journal and Jabatan Arkib Negara and is essential in narrow down the process. The result shown the process of procurement management system in KLIA2 fail based on three aspects that is human management factor, process factor and contract and technical factor. In conclusion, procurement management system is important to project successes. Once procurement management system in KLIA2 have a problem and make the project are delays. Then it will improve the procurement process in mega project construction. The information of this study will be useful in managing procurement management system